Associations of Dietary Vitamin A and Beta-Carotene Intake With Depression. A Meta-Analysis of Observational Studies - Zhang, Yi; Ding, Jun; Liang, Jieyu (Frontiers in Nutrition, 2022)
Objective: To clarify the associations of dietary vitamin A and beta-carotene intake with depression based on a meta-analysis of observational studies. Methods: An extensive literature search on February 2022 (PubMed, Web of Science and Embase) was employed to identify observational studies on the associations of dietary vitamin A and beta-carotene intake with depression. The pooled relative risk (RR) of depression for the highest versus lowest dietary vitamin A and beta-carotene intake category, and the standard mean difference (SMD) of dietary vitamin A and beta-carotene intake for depression versus control subjects, were calculated. Results: A total of 25 observational studies (100955 participants), which included 24 cross-sectional/case-control and 1 prospective cohort study, were included in this study. The overall multi-variable adjusted RR demonstrated that dietary vitamin A intake was inversely associated with depression (RR=0.83, 95%CI: 0.70 to 1.00; P=0.05). In addition, the combined SMD showed that the dietary vitamin A intake in depression was also lower than that in control subjects (SMD=-0.13, 95%CI: -0.18 to -0.07; P<0.001). On the other hand, the overall multi-variable adjusted RR indicated that dietary beta-carotene intake was negatively associated with depression (RR=0.63, 95%CI: 0.55 to 0.72; P<0.001). The combined SMD showed that the dietary beta-carotene intake in depression was also lower than that in control subjects (SMD=-0.34, 95%CI: -0.48 to -0.20; P<0.001). Conclusions: Our results suggest that both dietary vitamin A and beta-carotene intake is inversely associated with depression. However, due to the limited evidence, further prospective cohort studies are still needed.